Optimization of Corner Reflector Antenna at 900 MHz – 2400 MHz for RF Energy Harvester System - Nurul Sinta Elysa, Radial Anwar, Yuyu Wahyu (International Journal of Advanced Science and Technology, 2020)
RF energy harvesting changes the radio wave to electrical energy. Some of sources are radio broadcasting and TV station, cellular base station and wireless network that can be harvested by antenna, one of antenna is corner reflector. This paper presents the design of corner reflector for RF energy harvesting with gain for 900 MHz, 1650 MHz, 1800 MHz, 2100 MHz and 2400 MHz is 4.11 dB, 7.29 dB, 4.45 dB, 9.09 dB and 7.22 dB.Keywords: Beamwidth; Corner Reflector, Energy Harvesting